New insights on the chemical composition and antimicrobial activity of rhizome essential oil from Vietnamese Cyperus stoloniferus Retz. (Cyperaceae) - Thai, Tran Huy; Rocchi, Francesca; Nguyen, Thi Hien; Trinh, Xuan Thanh; Nguyen, Quang Hung; Paoli, Mathieu; Bighelli, Ange; Casanova, Joseph (Academia Journal of Biology, 2024)
Cyperus stoloniferus Retz. is a perennial grass-like plant widely distributed in Vietnam. The composition of essential oil isolated from rhizomes has been investigated by a combination of chromatographic (Column chromatography, Gas chromatography in combination with retention indices) and spectroscopic techniques (Mass spectrometry, 13C NMR spectroscopy). Cyperene (15.8%), cyperotundone (12.9%) and α-cyperone (11.2%) were the major components. The composition of essential oil sample from this species in Vietnam differed substantially from that previously reported in China. C. stoloniferus rhizome essential oil displayed weak antibacterial activity against gram-negative bacteria, gram-positive bacteria, and yeasts.